On Dative-Lative Encoded Direct Objects in West Mansi - Gerson Klumpp (Linguistica Uralica, 2023)
Among the varieties of Ob-Ugric, West Mansi stands out in showing a differential object marking pattern in which direct objects may be encoded with a multi-functional dative-lative case. The present study builds on the West Mansi texts in the Ob-Babel corpus, where approximately one third of all referential and given objects is marked. As has been observed for other object marking varieties of Mansi too, the majority of marked objects agree with the verb. Object agreement signals topicality, but in focal contexts given objects also do not agree. A single parameter responsible for object marking could not be identified, and the results point to a bundle of parameters falling under the notions of prominence and activation. Grammaticalization of the dative-lative case as a marker of direct objects may result from topicalization, recipient promotion, and agent marking. The study contributes to the knowledge about DOM in Mansi, and adds West Mansi to the body of literature on accusative-dative syncretic DOM.